Complexion-mediated martensitic phase transformation in Titanium - J. Zhang (Nature Portfolio, 2017)
One way of tuning mechanical properties of alloys lies in utilizing athermal phase transitions. Here authors report a complexion-mediated martensitic transformation in Ti alloys yielding a nanolaminate structure of martensite bounded by planar complexions, promising new strategies for the design of high strength Ti alloys.